Functional Genomics for the Identification of Modulators of Platelet-Dependent Thrombus Formation - Vermeersch, Elien; Nuyttens, Benedicte P.; Tersteeg, Claudia; Broos, Katleen; De Meyer, Simon F.; Vanhoorelbeke, Karen; Deckmyn, Hans (TH Open, 2018)
Despite the absence of the genome in platelets, transcription profiling provides important insights into platelet function and can help clarify abnormalities in platelet disorders. The Bloodomics Consortium performed whole-genome expression analysis comparing in vitro–differentiated megakaryocytes (MKs) with in vitro–differentiated erythroblasts and different blood cell types. This allowed the identification of genes with upregulated expression in MKs compared with all other cell lineages, among the receptors BAMBI, LRRC32, ESAM, and DCBLD2. In a later correlative analysis of genome-wide platelet RNA expression with interindividual human platelet reactivity, LLRFIP and COMMD7 were additionally identified. A functional genomics approach using morpholino-based silencing in zebrafish identified various roles for all of these selected genes in thrombus formation. In this review, we summarize the role of the six identified genes in zebrafish and discuss how they correlate with subsequently performed mouse experiments.
Keywords: knockout mice; hemostasis; megakaryocytes; thrombosis; transgenic mice